2019
DOI: 10.2147/ndt.s209379
|View full text |Cite
|
Sign up to set email alerts
|

<p>Functional capacity as a predictor of postoperative delirium in transurethral resection of prostate patients in Northeast Brazil</p>

Abstract: IntroductionPostoperative delirium (POD) is a common disorder and its frequency varies from 15% to 25% after major elective surgery. There are few data on the incidence of POD in Brazil. Here, we sought to assess the incidence of POD following transurethral resection of the prostate (TURP) and to examine precipitating and predisposing factors associated.MethodWe performed a prospective observational study of elderly male patients undergoing TURP (N=55) in Northeast Brazil. Information on demographic, medical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Finally, five papers were included in our review, and the study characteristics are presented in Table 3 . The mean age of patients included in all studies was >70 years, four studies included patients undergoing transurethral resection of the prostate (TUR-P) [ 3 , 15 , 17 , 18 ], and only two studies assessed POD after TUR-BT [ 3 , 16 ]. The incidence of POD ranged from 1.2 to 21.2% depending on the assessment tool of delirium.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, five papers were included in our review, and the study characteristics are presented in Table 3 . The mean age of patients included in all studies was >70 years, four studies included patients undergoing transurethral resection of the prostate (TUR-P) [ 3 , 15 , 17 , 18 ], and only two studies assessed POD after TUR-BT [ 3 , 16 ]. The incidence of POD ranged from 1.2 to 21.2% depending on the assessment tool of delirium.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 5 , 15 ] compared the history of delirium (heterogeneity: P = .53, I 2 = 0). There was a significant difference between the 2 groups (95% CI: 1.63–29.86, P = .009) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 4 , 15 , 17 , 18 , 20 ] compared preoperative use of psychotropic substances (heterogeneity: P = .59, I 2 = 0). There was a significant difference between the 2 groups (95% CI: 1.11–3.52, P = .02) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…I have carefully read the study entitled "Functional capacity as a predictor of postoperative delirium in transurethral resection of prostate patients in Northeast Brazil" published in Neuropsychiatric Disease and Treatment by Braga et al, and his findings and conclusions are indeed interesting. 3 This study is one of the few studies which addresses the issue of PD. This study was a prospective observational study including 55 urologic patients, which suggested that loss of functional capacity was associated with PD in old patients following transurethral resection of the prostate.…”
mentioning
confidence: 99%